Peningkatan Hasil Belajar Tematik Terpadu Peserta Didik Menggunakan Pendekatan Value Clarification Technique (VCT) Model Matriks di Kelas V Sekolah Dasar - Juwita, Zulna; Arwin, Arwin (Universitas Negeri Padang, 2024)
This research is motivated by the difference between learning expectations and reality. This study aims to describe the increase in student learning outcomes using the Matrix Model Value Clarification Technique (VCT) approach in integrated thematic learning in class V SDN 23 Kamang, Sijunjung Regency. This type of research is classroom action research using qualitative and quantitative approaches. The subjects are teachers and students. The results showed an increase in lesson plans for cycle I with an average of 85.9% (B), and cycle II 97.72% (SB). Implementation on the teacher aspect of cycle I with an average of 79.7% (C), and cycle II 93.7% (SB), while on the student aspect of cycle I with an average of 78.1% (C), and cycle II 93.7% (SB). Student assessment in cycle I was 70.45 and in cycle II with an average of 86.34. In this study, it can be concluded that the Value Clarification Technique (VCT) Matrix Model approach can improve integrated thematic learning outcomes in grade V Elementary Schools.